Experimental Analysis for Nitrogen Oxide Reduction in a Diesel Engine by the Hydrogen-Assisted Selective Catalytic Reduction Technique. (24th January 2023) - Mathavan, S.; Nagarajan, G.; Murugan, Sivaraj
Abstract : Diesel engine emissions pose a serious threat to the environment and cause inevitable hazards to the atmosphere. The technique that is used to control and combat nitrogen oxide (NOX ) emissions is selective catalytic reduction. However, the various experimental conditions in the SCR technique will reduce NOX emissions. Former studies experimentally discovered the decrease of NOx discharges at a higher temperature. In this study, a two-cylinder diesel engine with a 34 kW rated power at 3750 rpm under low-temperature operating conditions underwent hydrogen-assisted selective catalytic reduction of NOx . The experiment was performed by differing the hydrogen injection duration (0–40°CA) and NOX emissions were studied. Variation in emissions with H2 injection was investigated. On varying the hydrogen injection duration, NOX, HC, CO2, CO, and smoke emissions are reduced (mention the % of reduction) and it can be applied in real time to reduce global warming.